Methane accumulation and its potential precursor compounds in the oxic surface water layer of two contrasting stratified lakes - Schroll, Moritz; Liu, Liu; Einzmann, Teresa; Keppler, Frank; Grossart, Hans-Peter (The science of the total environment, 2023)
Methane (CH4) supersaturation in oxygenated waters is a widespread phenomenon despite the traditional perception of strict anoxic methanogenesis. This notion has recently been challenged by successive findings of processes and mechanisms that produce CH4 in oxic environments. While some of the processes contributing to the vertical accumulation of CH4 in the oxygenated upper water layers of freshwater lakes have been identified, temporal variations as well as drivers are still poorly understood. In this study, we investigated the accumulation of CH4 in oxic water layers of two contrasting lakes in Germany: Lake Willersinnweiher (shallow, monomictic, eutrophic) and Lake Stechlin (deep, dimictic, eutrophic) from 2019 to 2020. The dynamics of isotopic values of CH4 and the role of potential precursor compounds of oxic CH4 production were explored. During the study period, persistent strong CH4 supersaturation (relative to air) was observed in the surface waters, mostly concentrated around the thermocline. The magnitude of vertical CH4 accumulation strongly varied over season and was generally more pronounced in shallow Lake Willersinnweiher. In both lakes, increases in CH4 concentrations from the surface to the thermocline mostly coincided with an enrichment in 13C-CH4 and 2H-CH4, indicating a complex interaction of multiple processes such as CH4 oxidation, CH4 transport from littoral sediments and oxic CH4 production, sustaining and controlling this CH4 supersaturation. Furthermore, incubation experiments with 13C- and 2H-labelled methylated P-, N- and C- compounds clearly showed that methylphosphonate, methylamine and methionine acted as potent precursors of accumulating CH4 and at least partly sustained CH4 supersaturation. This highlights the need to better understand the mechanisms underlying CH4 accumulation by focusing on production and transport pathways of CH4 and its precursor compounds, e.g., produced via phytoplankton. Such knowledge forms the foundation to better predict aquatic CH4 dynamics and its subsequent rates of emission to the atmosphere.
Gesehen am 05.12.2023